1997
DOI: 10.1093/ije/26.1.146
|View full text |Cite
|
Sign up to set email alerts
|

Who are the 'low energy reporters' in the dietary and nutritional survey of British adults?

Abstract: These results suggest that LER may be overrepresented within specific population subgroups and that underreporting bias may not be food and nutrient neutral. This has implications for the design and interpretation of studies of diet and disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
177
6
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(205 citation statements)
references
References 12 publications
18
177
6
4
Order By: Relevance
“…Based on the low energy intake, this group could also be called a low food energy group or low energy reporter (LER) group. Other studies have reported higher BMI in low energy groups (Pryer et al, 1997(Pryer et al, , 2001Fraser et al, 2000), but we did not find the same tendency in our LER group. However, we found a somewhat higher percentage of Bold numbers marks cluster with highest intake, underlined numbers marks clusters with lowest intake.…”
Section: Discussioncontrasting
confidence: 99%
“…Based on the low energy intake, this group could also be called a low food energy group or low energy reporter (LER) group. Other studies have reported higher BMI in low energy groups (Pryer et al, 1997(Pryer et al, , 2001Fraser et al, 2000), but we did not find the same tendency in our LER group. However, we found a somewhat higher percentage of Bold numbers marks cluster with highest intake, underlined numbers marks clusters with lowest intake.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, the diet quality indices may be affected positively or negatively depending on the nutritional profile of the 'forgotten' food items in the 24-hour food recalls. The proportion of LERs is however similar to that found in the British population, although we did not find demographic, socio-economic or BMI differences between LERs and other subjects, unlike Pryer et al 45,46 . Nevertheless, the high proportion of overweight (46%) and obesity (22%) in our sample suggests that many subjects likely consume more energy than they need.…”
Section: Dietary Patterns According To Length Of Stay In Canada and Sessupporting
confidence: 83%
“…This procedure, known as the Goldberg cut-off technique, has demonstrated a widespread tendency to underestimation in large national dietary surveys from several countries as well as in many smaller surveys (Heywood et al, 1993;Fogelholm et al, 1996;Briefel et al, 1997;Lafay et al, 1997;Price et al, 1997;Pryer et al, 1997;Rothenberg et al, 1997;Voss et al, 1998). However, this technique was devised to evaluate the overall bias towards under-reporting at the group level.…”
Section: Introductionmentioning
confidence: 99%